The role of perineurium in modern reconstructive-renewing surgery of peripheral nerves - Yuriy Lisaychuk; Valeriy Bovkun; Oleg Goncharuk; Roman Chetverus; Iryna Savitskaya (Ukrainian Neurosurgical Journal, 2011)
Own experience of perineurium features research in modern reconstructive-renewing microsurgery of damaged peripheral nerves is presented. In experimental part of the peripheral nerves research carried out on 102 rats interrelation of perineurium and axon tissue at fascicular (perineural) stitch were studied, quality of direct muscle neurotisation and procedure of end-to-side nerve’s stitch were improved. In clinical part of the research specific features of microsurgical nerve stitch, and also of direct muscle neurotisation are given that approve feasibilities of end-to-side connection of peripheral nerves.